HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR SISWI MADRASAH ALIYAH (MA) YAYASAN DINIYAH PUTERI PEKANBARU - Eniwati Khaidir (Kutubkhanah, 2016)
This study aims to investigate the relationship between emotional intelligence and academic achievement of student Madrasah Aliyah (MA) at Diniyah Puteri Foundation Pekanbaru. The total population in this study was 62 students. Because of population is small,the entire population is taken as sample. Data were collected through a questionnaire and documentation, analyzed by descriptive and inferential statistics. The results showed a significant relationship between emotional intelligence and academic achievement of students of Madrasah Aliyah Diniyyah Puteri Pekanbaru. To develop and optimize the emotional intelligence it is recommended to the school, especially the teachers in order to incorporate elements emosioal intelligence in presenting the material as well as emotionally engaging students in the learning process